MIDSHIPS: Multicentre Intervention Designed for Self-Harm using Interpersonal Problem-Solving: protocol for a randomised controlled feasibility study - Collinson, Michelle; Owens, David; Blenkiron, Paul; Burton, Kayleigh; Graham, Liz; Hatcher, Simon; House, Allan; Martin, Katie; Pembroke, Louise; Protheroe, David; Tubeuf, Sandy; Farrin, Amanda (Université d'Ottawa | University of Ottawa, 2014)
Abstract Background Around 150,000 people each year attend hospitals in England due to self-harm, many of them more than once. Over 5,000 people die by suicide each year in the UK, a quarter of them having attended hospital in the previous year because of self-harm. Self-harm is a major identifiable risk factor for suicide. People receive variable care at hospital; many are not assessed for their psychological needs and little psychological therapy is offered. Despite its frequent occurrence, we have no clear research evidence about how to reduce the repetition of self-harm. Some people who have self-harmed show less active ways of solving problems, and brief problem-solving therapies are considered the most promising psychological treatments. Methods/Design This is a pragmatic, individually randomised, controlled, feasibility study comparing interpersonal problem-solving therapy plus treatment-as-usual with treatment-as-usual alone, for adults attending a general hospital following self-harm. A total of 60 participants will be randomised equally between the treatment arms, which will be balanced with respect to the type of most recent self-harm event, number of previous self-harm events, gender and age. Feasibility objectives are as follows: a) To establish and field test procedures for implementing the problem-solving intervention; b) To determine the feasibility and best method of participant recruitment and follow up; c) To assess therapeutic delivery; d) To assess the feasibility of obtaining the definitive trial’s primary and secondary outcomes; e) To assess the perceived burden and acceptability of obtaining the trial’s self-reported outcome data; f) To inform the sample size calculation for the definitive trial. Discussion The results of this feasibility study will be used to determine the appropriateness of proceeding to a definitive trial and will allow us to design an achievable trial of interpersonal problem-solving therapy for adults who self-harm. Trial registration Current Controlled Trials ( ISRCTN54036115 )